Pengaruh corporate governance, profitability, dan foreign ownership terhadap dividend policy pada perusahaan manufaktur yang terdaftar di bursa efek indonesia Periode 2014-2016 - Bangun, Nurainun; Yuniarwati, Yuniarwati; Santioso, Linda (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2018)
The purpose of this research is to analyze the effect of corporate governance, profitability, and foreign ownership on dividend policy. This research uses manufacturing company listed in Indonesia Stock Exchange for the period 2014-2016 as the population. Using purposive sampling, 95 data are selected as samples. Data processing in this research uses software program IBM SPSS version 23. The result shows that board size have a significant effect on dividend policy. Board independence do not have a significant effect on dividend policy. CEO duality do not have a significant effect on dividend policy. Profitability have a significant effect on dividend policy. Foreign ownership have a significant effect on dividend policy.